hZIP1 Inhibits Progression of Clear Cell Renal Cell Carcinoma by Suppressing NF-kB/HIF-1α Pathway - Zhan, Bo; Dong, Xiao; Yuan, Yulin; Gong, Zheng; Li, Bohan (Frontiers in Oncology, 2021)
Purpose: Accumulating literature has suggested that hZIP1 and HIF-1α play vital roles in the tumor process of clear cell renal cell carcinoma (ccRCC). However, the functional roles of hZIP1 and HIF-1α in ccRCC remain largely unknown.. Methods: HIF-1α protein level was evaluated by western blot in ccRCC tissues and cell lines. ccRCC cell lines were transfected with HIF-1α-siRNA to down-regulate the expression level of HIF-1α. Then the proliferative, migratory and invasive abilities of ccRCC cells in vitro were detected by real-time cell analysis (RTCA) assay, wound healing assay and transwell assay, respectively. The role of HIF-1α in vivo was explored by tumor implantation in nude mice. Then the effect on glycolysis‐related proteins was performed by western blot after hZIP1 knockdown (overexpression) or HIF-1α knockdown. The effect on NF‐kB pathway was detected after hZIP1 overexpression. Results: HIF-1α was markedly downregulated in ccRCC tissues compared with normal areas. But HIF-1α presented almost no expression in HK-2 and ACHN cells. Immunofluorescence indicated HIF-1α and PDK1 expression in both the cytoplasm and nucleus in ccRCC cells. Downregulation of HIF-1α suppressed ccRCC cell proliferation, migration and invasion and resulted in smaller implanted tumors in nude mice. Furthermore, hZIP1 knockdown elevated HIF-1α protein levels and PDK1 protein levels in ccRCC cells. Interestingly, a sharp down-regulated expression of HIF-1α was observed after hZIP1 overexpression in OSRC-2 and 786-O cells, resulted from a downtrend of NF-kB1 moving into the cell nucleus. Conclusion: Our work has vital implications that hZIP1 suppresses ccRCC progression by inhibiting NF-kB/HIF-1α pathway.